Política pública de educação do campo: análise no movimento da licenciatura em educação do campo na UFMA - Martins, Izabel Cristina (2020)
This study has as object of research the Public Policy of Education of the Field, materialized through the course of Degree in Education of the Field - that is offered by the Federal University of Maranhão - UFMA Campus III of Bacabal. The objective is to analyze the risks and potentials that arose during the development of the pedagogical didactic actions of the same. At first, we tried to situate the context of research and Rural Education in the state to understand the movement that surrounds the object of study. It is a case study, with a qualitative approach, anchored in bibliographic sources that give theoretical basis to the study in question. Conversations and documentary analysis were used for data collection. The thematic axes emerged from the state of the art realized in the productions on the theme. The results of the research pointed to the materialization of the course, consolidated from the strengthening of actions, the collective movements of struggles, the holding of seminars, meetings and the published academic production that constitute potential for Rural Education and teacher training of the field in the state.